Association between heavy metals and risk of cardiovascular diseases in US adults with prediabetes from NHANES 2011–2018 - Sijia Yang; Zhuoshuai Liang; Yue Qiu; Xiaoyang Li; Yuyang Tian; Yawen Liu (BMC Public Health)
Abstract Background The association of plasma metals on the risk of cardiovascular diseases (CVD) in adults with prediabetes remains poorly investigated. To assess the association between plasma metal exposure and the risk of CVD in prediabetic adults in the United States using five plasma metals. Methods Five cycles of data (2011–2012, 2013–2014, 2015–2016, and 2017–2018) from the NHANES were adopted in this study. The plasma metals were measured in 1088 participants with prediabetes. We utilized multivariate logistic regression, WQS, and BKMR models to evaluate the associations between the five plasma metals and the risk of CVD. Results The risk of CVD in participants with prediabetes were found to link to the 2nd quartile, 3rd and 4th quartiles of cadmium on the basis of multivariate logistic model (OR = 3.03, 95%CI: 1.17–7.82, P<0.01). Moreover, the joint effect of the five metals on the risk of CVD participants with prediabetes were unveiled using WQS and BKMR models (OR = 1.79, 95%CI: 1.15–2.77, P<0.01). In addition, when the concentrations of the other four metals were controlled at the 25th, 50th, and 75th percentile, correspondingly, cadmium had a statistically significant positive association with the risk of CVD. Conclusion The exposure of metals documented by the five metals links to the risk of CVD in participants with prediabetes in the United States. Among all the five metals, cadmium has the strongest association with the risk of CVD in participants with prediabetes.